On Normalization of Singular Integral Operators with Linear Fractional Carlemann Shift (Texas Journal of Multidisciplinary Studies, 2022)
The article considers the normalization problem for singular integral operators with Carleman shift in the case when the symbol of the operator vanishes at the end points of the contour